2019
DOI: 10.1371/journal.pone.0224701
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light and nitrogen availability on photosynthetic efficiency and fatty acid content of three original benthic diatom strains

Abstract: Microalgal biotechnology has gained considerable importance in recent decades. Applications range from simple biomass production for food and animal feed to valuable products for fuel, pharmaceuticals, health, biomolecules and materials relevant to nanotechnology. There are few reports of the exploration of wider microalgae biodiversity in the literature on high value microalgal compounds, however, because it is believed that there is little to be gained in terms of biomass productivity by examining new strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 100 publications
(133 reference statements)
1
32
0
2
Order By: Relevance
“…Cointet et al [ 38 ] reported that FAME from Entomoneis paludosa, Nitzschia alexandrina and Staurosira sp. directly undergo transesterification using hydrochloric methanol and chloroform as solvent.…”
Section: Microalgae Lipids and Fatty Acids Extraction Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cointet et al [ 38 ] reported that FAME from Entomoneis paludosa, Nitzschia alexandrina and Staurosira sp. directly undergo transesterification using hydrochloric methanol and chloroform as solvent.…”
Section: Microalgae Lipids and Fatty Acids Extraction Methodsmentioning
confidence: 99%
“…The studies reported that the most abundant saturated fatty acid (SFA) was palmitic acid (C16:0), ranging from 32.5 ± 4.3% to 64.6 ± 6.0% for all strains in nitrogen-limited treatment. Whereas, the highest unsaturated fatty acid was oleic acid for E. paludosa (20.1 ± 3.2%) and palmitoleic acid for N. alexandrina and Staurosira sp., with 25.2 ± 1.9% and 25.0 ± 9.0%, respectively [ 38 ].…”
Section: Microalgae Lipids and Fatty Acids Extraction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Culture system is another relevant aspect to take into consideration in biomolecule production and nutrient limitation studies. Although due attention is put into it in engineering, it is surprisingly overlooked in basic science research, with the great majority of it being conducted in batch cultures (Cointet et al, 2019; Ethier et al, 2011; Matos et al, 2014; Negi et al, 2016; Zhao et al, 2017). Nevertheless, the importance of continuous cultivation on nutrient limitation studies can hardly be overstated.…”
Section: Introductionmentioning
confidence: 99%
“…Although due attention is put into it in engineering, it is surprisingly overlooked in basic science research, with the great majority of it being conducted in batch cultures (Cointet et al, 2019;Ethier et al, 2011;Matos et al, 2014;Negi et al, 2016;Zhao et al, 2017).…”
mentioning
confidence: 99%